Integrated metabolic and transcriptomic profiles reveal the germination‐associated dynamic changes for the seeds of Cassia obtusifolia L. Issue 2 (12th January 2023) - Chen, Biying; Shi, Biru; Ge, Xiaoyan; Fu, Zhifei; Yu, Haiyang; Zhang, Xu; Liu, Caixiang; Han, Lifeng
Abstract: Introduction: The seeds of Cassia obtusifolia L. ( Cassiae [ C .] semen) have been widely used as both food and traditional Chinese medicine in China. Objectives: We aimed to analyze the metabolic mechanisms underlying C . semen germination. Materials and Methods: Different samples of C . semen at various germination stages were collected. These samples were subjected to 1 H‐NMR and UHPLC/Q‐Orbitrap‐MS‐based untargeted metabolomics analysis together with transcriptomics analysis. Results: A total of 50 differential metabolites (mainly amino acids and sugars) and 20 key genes involved in multiple pathways were identified in two comparisons of different groups (36 h vs 12 h and 84 h vs 36 h). The metabolite–gene network for seed germination was depicted. In the germination of C . semen, fructose and mannose metabolism was activated in the testa rupture period, indicating more energy was needed (36 h). In the embryonic axis elongation period (84 h), the pentose and glucuronate interconversions pathway and the phenylpropanoid biosynthesis pathway were activated, which suggested some nutrient sources (nitrogen and sugar) were in demand. Furthermore, oxygen, energy, and nutrition should be supplied throughout the whole germination process. These global views open up an integrated perspective for understanding the complex biological regulatory mechanisms during the germination process of C . semen. Abstract : The seeds ( Cassiae semen) of Cassia obtusifolia L. have been widely used as traditional medicine in China. For better understanding the metabolic mechanism along with germination, seed samples of Cassiae semen at various germinating stages were analyzed. In the germination of C. semen seeds, energy was more needed in the testa rupture period, and some nutrient sources were demanded in the embryonic axis elongation period. Furthermore, oxygen, energy and nutrition should be supplied through the whole germination process.